(untitled) (Bioscience Journal, 2015)
In this study the effect of carbon dioxide on the physiological and sanitary quality of rice seed during storage is reported. The experimental design was completely randomized in a 2x3x3 factorial arrangement, with two cultivars (Irga 423 and 424), three concentrations of carbon dioxide (0, 25 and 50%) and three storage periods (15, 30 and 45 days). According to the results, it was found that carbon dioxide maintains germination and vigor, and reduces mycoflora associated with the seed. The incidence of Aspergillus sp., Fusarium sp. and Rhizoctonia sp. was reduced respectively in proportions of 50%, 75% and 100%, when the seeds were submitted to the a 50% concentration of carbon dioxide for 45 days storage. As regards seed-seedling transmission, only the fungus was able to promote Bipolaris sp. disease in seedlings from seeds treated with carbon dioxide. In this context, carbon dioxide is a viable alternative for maintaining the quality of rice seeds during storage.